ESSENTIALS OF PROJECT INITIATION PHASE - Farkhodov Jamshid Jurabek ugli; Kurbanova Maftuna Lazizovna (Web of Journals Publishing, 2024)
This article is about one of the crucial phases of the project life cycle - the project initiation phase and its important parts. Project initiation is a success base for any project.
Keywords: project scope, RACI chart, project charter, business case, feasibility analysis.